Knowledge and practices regarding hand-washing among mothers of children less than five years of age in rural areas of District Sialkot - Sonia Almas; Ayesha Babar Kawish; Tahir Mehmood Butt; Subhana Akber Khan (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To assess knowledge and practices regarding hand-washing among mothers of children aged ?5 years. Methods: The cross-sectional study was conducted from March to July 2015 in rural areas of Union Council Charwa, Tehsil Pasrur in District Sialkot, Pakistan, and comprised mothers of children aged ?5 years. Data was collected using a pre-tested and validated structured questionnaire developed in line with World health Organisation guidelines on hand-washing technique. Data was analysed using SPSS 17. Results: Of the 422 subjects, 319 (75.4%) had sufficient knowledge and 104 (24.6%) showed good practices regarding hand-washing. However, only 59 (14%) mothers were found adherent to the appropriate technique of hand-washing. Conclusion: Health education and behaviour-changing communication approaches must be implemented to educate the masses about proper hand-washing technique. Key Words: Knowledge, Practices, Hand-washing, Mothers, Health education, Pakistan.